Book Review: “Ermil i Stratonik. Sveti ranohrišćanski mučenici beogradski (Ермил и Стратоник. Свети ранохришћански мученици београдски)”, ed. Dubravka Preradović (Дубравка Прерадовић), Balkanološki Institut Srpske akademije nauka i umetnosti, Belgrade - BUNDRA, Traian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2022)
This year, the Institute for Balkan Studies of the Serbian Academy of Sciences and Arts published a collection of papers about “Hermylos and Stratonikos. Early Christian martyrs of Belgrade”, edited by Ph.D. Dubravka Preradović, research asso¬ci¬ate of the institute.